The impact of human development on the Romanian life insurance market: A county spatial econometric analysis - Codru÷ta Mare; Simona Laura Drago÷s; Ingrid-Mihaela Dragotæa (Cogent Business & Management, 2019)
This work adds to the debate on the determinants of the demand for life insurance providing new insights for the unexplored Romanian market, and the new perspective of spatial econometric analysis. Results show that there are spatial interactions between the Romanian counties regarding the life insurance density, positively and significantly conditioned by the level of the local human development. The latter is included in the analysis in the form of the Local Human Development Index (LHDI) developed and computed for the Romanian counties and update for this study. The spatial econometrics regression models emphasize significant diffusion and contagion processes on the local Romanian life insurance market. We also identified a significant positive impact of income, urbanization and medical staff over the life insurance demand.
Keywords: C21; C31; G22; I32; 650; life insurance market; local human development; county spatial processes